PEMANFAATAN MEDIA VLOG (VIDEO BLOGGING) LINGKUNGAN SEKITAR UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN MENYUSUN TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 3 MADIUN - Fahrani Faqihhana Fiddini; Dwi Rohman Soleh; Herman Trisna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the use of environment-based vlog (video blogging) media to enhance the learning motivation and descriptive text writing skills of Grade VII E students at SMP Negeri 3 Madiun. The study was motivated by low learning motivation and students’ limited ability to transform observations into coherent descriptive texts. It employed the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles with 31 participants (16 male and 15 female students). Data were collected through observation, learning motivation questionnaires, descriptive text writing performance tests, and documentation, then analyzed using both quantitative and qualitative descriptive methods. The results showed consistent improvement across cycles. In the pre-action stage, only 12 out of 31 students (38.7%) met the Learning Objective Achievement Criteria (KKTP). Following instruction using vlog media in Cycle I, the number of students meeting the criteria rose to 20 (64.5%), and further increased to 26 (83.9%) in Cycle II. The average learning motivation score also improved from 61.4 (moderate category) at the pre-action stage to 84.6 (high category) by the end of Cycle II. These findings indicate that most students gained a better understanding of the structure and linguistic features of descriptive texts and became more skilled at composing them after personally experiencing the processes of observation and vlog production. Thus, environment-based vlog media proved effective as an innovative alternative for teaching descriptive text writing—one that is contextual and relevant to the characteristics of digital-generation students.